Effect of 10% lemongrass (Cymbopogon citratus) and 3% hydrogen peroxide solution immersion on the dimensional stability of alginate impression - Indriani, Lenni; Habar, Ike Damayanti; Sonda, Angelitha Patricia (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Pathogenic bacteria can easily spread through impression materials, especially alginate. One of the chemicals disinfection agents used is hydrogen peroxide and natural disinfection alternatives, such as the decoction of lemongrass leaves. The aim of this study is to determine the effect of immersing Alginate impression in a disinfection solution of lemongrass (Cymbopogon citratus) and 3% hydrogen peroxide on the dimensional stability. The samples of this research consisted of 27 alginate impression samples of the upper jaw teeth prepared by manipulating alginate powder with water according to the manufacturer’s ratio and a lemongrass solution prepared by boiling 300 grams of lemongrass leaves 3000 ml of distilled water to obtain 300ml of lemongrass leaf decoction. The 27 samples were divided into three groups: the control group soaked in aquadest, one group soaked in 3% hydrogen peroxide, and one group soaked in 10% lemongrass decoction. The dimensional stability was measured by using a caliper for the horizontal dimension and then analyzed by using the Kruskal-Wallis test. This statistical analysis found a p-value of <0.05 in the horizontal dimension, indicating a difference in the horizontal dimensional stability of the alginate impression after immersion among the hydrogen peroxide, lemongrass leaves (C. citratus), and control groups. Further comparisons among the groups by using the Mann-Whitney Test resulted in a p-value of <0.05 for all the comparisons among the horizontal dimension of the groups. The dimensional changes of the alginate impression were slightly larger in the immersion of 10% lemongrass solution compared to the 3% hydrogen peroxide solution.